Thermodynamics of a scale‐invariant nonlinear sigma model. Issue 1 (21st December 2022) - Ferrari, Gabriel
Abstract: A recently developed variational resummation technique incorporating renormalization group properties has been shown to solve the scale dependence problem that plagues the evaluation of physical observables. This method is used in the present work to evaluate thermodynamical quantities within the two‐dimensional nonlinear sigma model, which shares some features with Yang‐Mills theories like asymptotic freedom, trace anomaly, and the nonperturbative generation of a mass gap. Besides the fact that nonperturbative results can be readily generated solely by considering lowest‐order contributions, we also show that its next‐to‐leading correction indicates convergence to the sought‐after scale invariance.